The Regulation of South Africa's Emerging Hydrocarbon Sector: A purposive analysis of the Upstream Petroleum Resources Development Act 23 of 2024 compared to the Mineral and Petroleum Resources Development Act 28 of 2002 - Davids, Mogammed Wafiq (Centre for Law and Society, 2025)
This thesis compares South Africa's hydrocarbon regulatory provisions per the Mineral and Petroleum Resources Development Act 28 of 2002 (MPRDA) and the recently enacted Upstream Petroleum Resources Development Act 23 of 2024 (UPRDA). Reform of South Africa's hydrocarbon regulatory framework was prompted by natural gas discoveries in the offshore Outeniqua Basin and the Karoo's shale gas reserves. South Africa's emerging hydrocarbon sector signals opportunities for widespread socio-economic development. Thus, understanding the purpose and function of South Africa's hydrocarbon regulatory framework is crucial for navigating South Africa's emerging sector. The MPRDA and the UPRDA entrust hydrocarbon resources to the state for public benefit, compelling similar objectives for its regulation and exploitation. Regulatory objectives envisage transformation, sustainable development, and socio-economic development. However, while the MPRDA and the UPRDA have similar regulatory objectives, different approaches are deployed to achieve them. The question driving this thesis is how South Africa's hydrocarbon legal framework should be understood to advance public benefit. Both legislative pieces are examined textually and contextually to determine their meaning and application. This thesis argues that indigenous hydrocarbons can provide the socio-economic boost South Africa needs for the population to advance. However, the regulatory objectives contained in both legislative texts provide insight into what public benefit should be expected from domestic hydrocarbon exploration and production and must be supported when domestic hydrocarbon rights are granted to oil companies. The legal analysis conducted in this thesis concludes that the UPRDA places South Africa in a better regulatory position to achieve the regulatory objectives and realise the public benefits of hydrocarbon extraction